The quest for prosperity how developing economies can take off - Lin, Justin Yifu. (Princeton Princeton University Press, 2012)
How can developing countries grow their economies? Most answers to this question center on what the rich world should or shouldn't do for the poor world. In The Quest for Prosperity, Justin Yifu Lin--the first non-Westerner to be chief economist of the World Bank--focuses on what developing nations can do to help themselves.
Includes bibliographical references (p. 287-308) and index.
Keywords: Developing countries--Economic conditions